DIRECTIVE SPEECH ACTS IN SONIC THE HEDGEHOG MOVIE SCRIPT (2020) BY JOSH MILLER - Palupi, Fitri; Andari, Ayu (Journal of English Education and Enterpreneurship (JEEP), 2021)
Directive speech acts is the kind of speech acts which is used by the speaker toget someone else to do something. This research analyzes Directive speech acts in Sonic the Hedgehog Movie Script by Josh Miller. The aim of this research is to find out the kinds and forms of directive speech acts in Sonic the Hedgehog Movie Script. Directive speech acts is the object of this research. Sonic the hedgehog movie script (2020) by Josh Miller is the subject of this research. Descriptive qualitative is a method of this research. The result of this research shows that five types of directive speech acts using Searle theory. The result of this research indicates thatthere are 82 utterances of directive speech acts. The researcher classify directive speech acts and divide into five including 54 commands, 11 request, 9 suggest, 6 warning and 2 inviting. Therefore, the researcher classifies directive speech acts that found into three forms they are 52 data imperative, 10 data interrogative and 20 data declarative. The researcher concludes that command and imperative is the dominant utterance of directive speech acts.